Aetiology, prophylaxis and management of preeclampsia - Gronkowska, Karolina (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2021)
Although preeclampsia affects approximately 3%–8% of pregnancies worldwide and is a major contributor to maternal and neonatal mortality and morbidity, the aetiology of preeclampsia is still not fully understood. This review presents the current knowledge on the aetiology of preeclampsia, with a special emphasis on risk factors and their role, and describes recommendations for the prevention and treatment of preeclampsia.